2011
DOI: 10.1016/j.mambio.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

No inbreeding effects on body size in two captive endangered gazelles

Abstract: a b s t r a c tSelection for body size is intricate, involving trade-offs between energy costs, reproductive output, foraging efficiency, and interaction with other community members. In dimorphic, polygynous ungulates, body size is highly correlated with reproductive success in both sexes. Body size has been proposed as a potential phenotypic indicator of genetic change, in wild and in captive populations. We analysed the relationship between adult body size and inbreeding in two captive populations of endang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…However, later on in the breeding programme some authors failed to find inbreeding depression in this same population. Ibáñez et al [ 30 ] did not find any inbreeding effect on body weight. Similarly, Ruiz-López et al [ 31 ] and Ibáñez et al [ 32 ] showed that neither mother nor offspring inbreeding had any effect on juvenile mortality.…”
Section: Introductionmentioning
confidence: 96%
“…However, later on in the breeding programme some authors failed to find inbreeding depression in this same population. Ibáñez et al [ 30 ] did not find any inbreeding effect on body weight. Similarly, Ruiz-López et al [ 31 ] and Ibáñez et al [ 32 ] showed that neither mother nor offspring inbreeding had any effect on juvenile mortality.…”
Section: Introductionmentioning
confidence: 96%
“…Even when inbreeding increased, there was no depression, as juvenile survival progressively increased over the 35-year study period. The low impact of inbreeding depression observed in our study (see also Ib añez et al 2011Ib añez et al , 2013 could be a consequence of a slow rate of inbreeding in the Cuvier's gazelle population in the past, which may have allowed natural selection to progressively purge some of the negative consequences of inbreeding (Ballou 1997), or it could just be a specific feature of the species, where the consequences of inbreeding seem to be less striking than in others (Ballou 1994). Improvements in husbandry may lead to higher average survival in captive populations in spite of an increase in inbreeding as well (Kalinowski et al 1999).…”
Section: Influence Of Inbreedingmentioning
confidence: 70%
“…One explanation may be that the number of founder individuals and pedigree reconstruction of the captive gazelle populations in previous studies were not the same as ours. Ours is based on new genetic findings (Ruiz‐López et al ., ) and recent studbook information (see also Ibáñez, Moreno & Barbosa, ; Moreno, Ibáñez & Barbosa, ).…”
Section: Discussionmentioning
confidence: 92%